Indicadores microbiológicos em áreas de cultivo de soja no estado de Mato Grosso - Aguillera, Luís Alberto (2020)
Microbiological variables are important for determining soil quality, which can be expressed through indexes. The soil microbiological quality index (SMQI) reflects the capacity that a soil would have to produce profitable crops, insuring the sustainability of the productive system. Therefore, the objective of this study was to evaluate soil microbiological quality indicators in areas of high (> 70 sc ha-1), medium (60 to 70 sc ha-1) and low (<60 sc ha-1) soybean productivity in the state of Mato Grosso (MT). For this purpose, soil samples were collected (depth 0-20 cm) in 61 soybean production areas in the state of MT, in which nematological analyzes and analyzes of soil enzymes were carried out. The following microbiological attributes were evaluated: populations of Pratylenchus brachyurus, Meloidogyne spp., Heterodera glycines, Helicotylenchus dihystera, Rotylenchulus reniformis and nematode eggs in the roots and soil, β-glucosidase enzyme, acid phosphatase enzyme and arylsulfatase enzyme. Through principal component analysis (PCA), it was determined which variables had correlations with the components and the SMQI was determined. PCA showed that the enzyme arylsulfatase is an important variable for discriminating areas of high, medium and low productivity. The other variables did not discriminate between high, medium and low productivity areas. The nematodes H. glycines, H. dihystera and P. brachyurus, both in the root and in the soil, correlate negatively (Spearmam correlation) with the SMQI. The enzymes β-glycosidase, and arylsulfatase correlated positively with the productivity (high, medium and low) of the studied areas, revealing to be good variable indicators for soil quality. The SMQI Enzymes, which only considers the variables related to the enzymatic activity, allowed to differentiate the soil quality in the studied areas where the soil of the areas with high and medium productivity were classified as medium quality, and the soil of the areas with low productivity were classified as low quality.